Does Marriage Pay More than Cohabitation? Selection and Specialization Effects on Male Wages in Germany - Katherin Barg; Miriam Beblo (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Empirical research has unambiguously shown that married men receive higher wages than unmarried, whereas a wage premium for cohabiters is not as evident yet. Our paper exploits the observed difference between the marital and the cohabiting wage premium in Germany and thus provides new insights into their respective sources, typically explained by specialization (husbands being more productive because their wives take over household chores) or selection (high earnings potentials being more attractive on the marriage market). We analyze the cohabiting and the marital wage premium in Germany using a shifting panel design for marriages and move-ins from 1993 to 2004 in the German Socio-Economic Panel. With non-parametric matching models we match men who get married (treatment group I) with cohabiting or single men (control groups) and men who move in with a partner (treatment group II) with singles. Matching reveals that higher wages are mostly due to positive selection - into marriage as well as into cohabitation. Supplementary analysis of intra-household time use suggests that specialization, if any, is part of the selection process from single to cohabitation to marriage.
Keywords: J12; J31; 330; Marital wage premium; cohabitation; matching approach